Programming of cardiac metabolism by miR-15b-5p, a miRNA released in cardiac extracellular vesicles following ischemia-reperfusion injury - Lucas C. Pantaleão; Elena Loche; Denise S. Fernandez-Twinn; Laura Dearden; Adriana Córdova-Casanova; Clive Osmond; Minna K. Salonen; Eero Kajantie; Youguo Niu; Juliana de Almeida-Faria; Benjamin D. Thackray; Tuija M. Mikkola; et al. (Elsevier, 2024)
Objective: We investigated the potential involvement of miRNAs in the developmental programming of cardiovascular diseases (CVD) by maternal obesity. Methods: Serum miRNAs were measured in individuals from the Helsinki Birth Cohort (with known maternal body mass index), and a mouse model was used to determine causative effects of maternal obesity during pregnancy and ischemia-reperfusion on offspring cardiac miRNA expression and release. Results: miR-15b-5p levels were increased in the sera of males born to mothers with higher BMI and in the hearts of adult mice born to obese dams. In an ex-vivo model of perfused mouse hearts, we demonstrated that cardiac tissue releases miR-15b-5p, and that some of the released miR-15b-5p was contained within small extracellular vesicles (EVs). We also demonstrated that release was higher from hearts exposed to maternal obesity following ischaemia/reperfusion. Over-expression of miR-15b-5p in vitro led to loss of outer mitochondrial membrane stability and to repressed fatty acid oxidation in cardiomyocytes. Conclusions: These findings suggest that miR-15-b could play a mechanistic role in the dysregulation of cardiac metabolism following exposure to an in utero obesogenic environment and that its release in cardiac EVs following ischaemic damage may be a novel factor contributing to inter-organ communication between the programmed heart and peripheral tissues.